Family Planning in the Republic of Tajikistan: A narrative review from Soviet times to 2017 - Ellison Henry; Zarrina H. Juraqulova (University Library System, University of Pittsburgh, 2020)
Introduction: Tajikistan's dramatic shift from a high to a low fertility society has taken place over a little more than two decades. While some fertility beliefs remained the same throughout the rapid economic and political transitions of Tajikistan, other beliefs may have changed to respond to the financial realities of the newly independent and Central Asian republic, such as having fewer children. The objective of this review was to describe and analyze the state of family planning in the Republic of Tajikistan from Soviet period (1929-1991) until 2017. Methods: The review is based on materials obtained from various sources including Google Scholar and PubMed, relevant to family planning in Tajikistan, including government policies, open-access nationally representative data, journal articles, and program reports, identified through a selective search of Google Scholar and PubMed databases, and the grey literature.  Conclusion: This narrative review presents the history of family planning in Tajikistan, outlines an understanding of the health system context as it relates to family planning, and analyzes the latest national family planning policy (2017). The authors suggest further research is required to (a) understand the beliefs and practices related to family planning; and (b) define strategies to address the issue of unmet need of family planning services.